Best Paper Selection (Yearbook of Medical Informatics, 2018)
Boudellioua I, Mahamad Razali RB, Kulmanov M, Hashish Y, Bajic VB, Goncalves-Serra E, Schoenmakers N, Gkoutos GV, Schofield PN, Hoehndorf R. Semantic prioritization of novel causative genomic variants. PLoS Comput Biol 2017;13(4):e1005500 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/28414800/Galeota E, Pelizzola M. Ontology-based annotations and semantic relations in large-scale (epi)genomics data. Brief Bioinform 2017;18(3):403-12 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/27142216/Khan Y, Saleem M, Mehdi M, Hogan A, Mehmood Q, Rebholz-Schuhmann D, Sahay R. SAFE: SPARQL Federation over RDF Data Cubes with Access Control. J Biomed Semantics 2017;8(1):5 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/28148277/Notaro M, Schubach M, Robinson PN, Valentini G. Prediction of Human Phenotype Ontology terms by means of hierarchical ensemble methods. BMC Bioinformatics 2017;18(1):449 https://www.ncbi.nlm.nih.gov/pmc/articles/pmid/29025394/Petegrosso R, Park S, Hwang TH, Kuang R. Transfer learning across ontologies for phenome-genome association prediction. Bioinformatics 2017;33(4):529-36 https://academic.oup.com/bioinformatics/article-lookup/doi/10.1093/bioinformatics/btw649